Filtering electrocardiogram: Music, math, and ST-elevation myocardial infarction - (:unkn) unknown (AVES, 2021)
Clinicians should have a basic understanding of the working principle of the instruments they use to avoid potential pitfalls caused by post-processing of the acquired biological signals. An electrocardiogram (ECG) is no exception; many different errors can arise during the acquisition or the processing of the ECG data, which may result in dangerous misdiagnoses. We present a case where the use of an inappropriate high-pass filter led to a false diagnosis of ST-elevation myocardial infarction. In addition, this report discusses the basic mechanisms of this frequently over-looked phenomenon and methods to avoid it.
Keywords: Acute coronary syndrome; artifacts; electrocardiogram; ST-elevation myocardial infarction